2019
DOI: 10.1051/matecconf/201930016008
|View full text |Cite
|
Sign up to set email alerts
|

A continuum based macroscopic unified low-and high cycle fatigue model

Abstract: In this work, an extension of a previously developed continuum based high-cycle fatigue model is enhanced to also capture the low-cycle fatigue regime, where significant plastic deformation of the bulk material takes place. Coupling of the LCF-and HCF-models is due to the damage evolution equation. The high-cycle part of the model is based on the concepts of a moving endurance surface in the stress space with an associated evolving isotropic damage variable. Damage evolution in the low-cycle part is determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Furthermore, Holopainen and co-workers [11,12] formulated a CTF model for transversely isotropic materials, as well as a CTF model for anisotropic materials where the damage is modeled as a tensor field [13]. An extension to include low-cycle fatigue has also been proposed [14]. Brighenti et al [15] suggested a more general expression for the endurance surface, and demonstrated fair agreement between modeled fatigue life and experimentally observed fatigue life for a range of steel alloys subjected to nonproportional stress.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Holopainen and co-workers [11,12] formulated a CTF model for transversely isotropic materials, as well as a CTF model for anisotropic materials where the damage is modeled as a tensor field [13]. An extension to include low-cycle fatigue has also been proposed [14]. Brighenti et al [15] suggested a more general expression for the endurance surface, and demonstrated fair agreement between modeled fatigue life and experimentally observed fatigue life for a range of steel alloys subjected to nonproportional stress.…”
Section: Introductionmentioning
confidence: 99%